A Data Scheduling Algorithm Based on Link Distance in Directional Aviation Relay Network - Zhou, Weiling; Li, Bo; Yan, Zhongjiang; Yang, Mao (Smart Grid and Internet of Things, 2021)
A data scheduling algorithm based on link distance is proposed in this paper, aiming at the problem of low data transmission throughput caused by the unequal link distance between aircraft relay nodes and ground nodes in a directional aviation relay network. Firstly, the aircraft node acquires the data transmission request of the ground node during the data transmission request collection stage, and measures the transmission distance and the data transmission delay with the ground node. Secondly, a data scheduling algorithm based on downlink first uplink, long distance first and short distance is designed, which fully utilizes the communication delay expansion gain brought by the unequal link distance. Finally, the simulation results show that when the network traffic is saturated, compared with the distributed scheduling (DS) algorithm, the algorithm named link distance data scheduling (LDDS) proposed in this paper improves the network throughput by 7.4%.